Cultural diversity shaped neolithic subsistence in the Carpathian Basin - M. L. C. Depaermentier; M. Kempf; E. Bánffy; K. W. Alt (Scientific Reports)
Abstract Stable carbon and nitrogen isotope analysis from archaeological human and animal bone collagen is a powerful tool to enlighten past socio-agricultural systems and their close links to environmental conditions. To assess whether isotopic patterns are a function of cultural behavior or rather determined by environmental diversity, we test the spatio-temporal effects of conditional and multivariate exploratory and environmental models on stable isotope variability in the Neolithic and Chalcolithic Carpathian Basin (6000–2800 BCE). Our results stress that variation in environmental settings influence both the isotope baselines and the subsistence strategies of early agricultural societies. Major shifts in isotopic patterns are, however, culturally-driven, which is particularly visible with the development and intensification of adapted agropastoral practices from 5500 − 5350 BCE and among the diet between different cultural groups. We conclude that socio-cultural diversity was the main driver of dietary habits and isotopic variability in early agropastoral societies of Neolithic Hungary.